Exposing the obscured influence of state-controlled media via causal inference of quotation propagation - Joseph Schlessinger; Richard Bennet; Jacob Coakwell; Steven Smith; Edward Kao (Scientific Reports)
Abstract Reporting by major media outlets influences news coverage by other outlets, resulting in an outsized impact on public opinion. Understanding this inter-outlet influence, known as intermedia agenda setting, is important for assessing the impact of state media and strategic communications. We demonstrate a novel method to quantify inter-outlet influence using causal inference on “quote following,” where one outlet uses the same quote as another outlet at a later date. By applying our methodology to a dataset of quotes from over 100,000 articles published in European media between May 2018 and October 2019, we reveal obscured influence by Russian state-affiliated media over other outlets and the general dynamics of European media. We find that Russian state-controlled media have a strong influence on the coverage of other Russian outlets, including independent outlets. Moreover, this influence extends to media ecosystems of other countries. Finally, we demonstrate quantifying inter-outlet influence on the specific topic of nuclear forces treaty, as an example of precision study of intermedia agenda setting on specific issues. Overall, our methodology quantifies sources and channels of influence between news outlets with important implications for strategic communication, influence operations, and media independence.